Perinatal Exposure to Methoxychlor Affects Reproductive Function and Sexual Behavior in Mice - Martini, Mariangela; Froment, Pascal; Franceschini, Isabelle; Pillon, Delphine; Guibert, Edith; Cahier, Claude; Mhaouty-Kodja, Sakina; Keller, Matthieu (Frontiers in Endocrinology, 2020)
Numerous chemicals derived from human activity are now disseminated in the environment where their exert estrogenic endocrine disrupting effects, and therefore represent major health concerns. The present study explored whether Methoxychlor (MXC), an insecticide with xenoestrogens activities, given during the perinatal period (from gestational day 11 to postnatal day 8) and at an environmentally dose (20µg/kg (body weight)/day), would affect reproductive physiology and sexual behavior of the offspring in mice. While MXC exposure did not induce any differences in the weight gain of animals from birth to 4 months of age, a clear difference (although in opposite direction according to the sexes) was observed on the anogenital distance between intact and exposed animals. A similar effect was also observed on preputial separation and vaginal opening, which reflects respectively in males and females, puberty occurence. The advanced puberty observed in females was associated with an enhanced expression of kisspeptin cells in the anteroventral periventricular region of the medial preoptic area. Exposure to MXC did not induce in adult females changes in the estrus cycle or in the weight of the female reproductive tract. By contrast, males showed reduced weight of the epididymis and seminiferous vesicles associated with reduced testosterone levels and seminiferous tubule diameter. We also showed that both males and females showed deficits in mate preference tests. As a whole, our results show that MXC impacts reproductive outcomes.